2011
DOI: 10.1111/j.1365-2982.2011.01675.x
|View full text |Cite
|
Sign up to set email alerts
|

Novel model of peripheral tissue trauma-induced inflammation and gastrointestinal dysmotility

Abstract: Background Trauma is a leading cause of death and although the gut is recognized as the “motor” of post-traumatic systemic inflammatory response syndrome and multiple organ failure, studies on the gastrointestinal tract are few. Our objectives were to create a precisely controllable tissue injury model in which gastrointestinal motility, systemic inflammation and wound fluid can be analyzed. Methods A non-narcotic murine trauma model was developed by the subcutaneous dorsal trans-implantation of a devitalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
3
12
0
Order By: Relevance
“…The peripheral tissue trauma model was described previously (15). Briefly, long bones, including muscles and rib cage with intercostal muscles, were isolated and minced (yielding TBX), and then implanted in the subcutaneous pouch of a healthy, syngenic, recipient mouse through a small (1 cm) incision.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The peripheral tissue trauma model was described previously (15). Briefly, long bones, including muscles and rib cage with intercostal muscles, were isolated and minced (yielding TBX), and then implanted in the subcutaneous pouch of a healthy, syngenic, recipient mouse through a small (1 cm) incision.…”
Section: Methodsmentioning
confidence: 99%
“…Animals were irradiated using a Precision X-ray 320 irradiator (North Branford, CT) at dose of 12.6 Gy (320 kV, 12.5 mA; 2 mm aluminum filter; HVL ~ 1 mm copper) and a dose rate of 1.58 Gy/min. Immediately after irradiation, mice were anesthetized with Isoflurane (Primal Healthcare Limited, Bethlehem, PA) and the surgical procedure for TBX implantation was performed (15). Kaplan-Meier survival curves were constructed for 7 days, at which time all surviving animals were euthanized.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Major surgery-evoked ischemia has been demonstrated to induce gastric mucosal injury and gastrointestinal dysmotility (1,2). Previous studies (3)(4)(5) have shown that the hypothalamic paraventricular nucleus and the lateral hypothalamic area (LHA) are two specific hypothalamic nuclei that modulate gastric activity and gastric mucosal injury.…”
Section: Introductionmentioning
confidence: 99%